Packaging Sardines Quality Control at PT. Sumber Mutiara Samudra Muncar Banyuwangi - Silviatul Hamidah; Siti Nur Aisyah Jamil (Samakia : Jurnal Ilmu Perikanan, 2025)
Fish lemuru is one of a fish that is often used as raw materials for sardines. One factor that is important to the packaging of sardines. Sardines in PT.Sumber Mutiara Samudra use two packs primary and secondary packaging and packaging. In canned often experienced disability as leaky, dent, double seam, bulges, blisters or scratch and rust. Hence the need of quality control the packaging in order to maintain the quality and safety. This research with the use of data in the descriptive observation, interview, and active participation. The result showed that disability can often happens in PT.Sumber Mutiara Samudra is the source of the leak, dent, double seam, and scratch. Disability is caused by the human factor, material, machine, and raw materials. The experience will be reject that disability is not marketable products.